The legionaries of Christ: Pederast network, power and transnational business corporation - Melgar B., Ricardo (2012)
The global dimension of pederasty is associated with sexual tourism, the business of child pornography and ecclesial pederasty, which has shocked the two Americas, although their transnational networks and power which are inherent have been insufficiently analyzed and discussed. We will make a case study of transnational ecclesial pederasty through the Legionaries of Christ order. The origins of this factual power and the perversions that meant, are among World War II and the beginnings of Cold War. We restore Marcial Maciel– its founder– to their power networks and complicity in a greater time span until breaking point. We discussed the real and symbolic weft of pederasty ecclesial through various categories and symbols: power, pain, purity, macula and the consciousness-altering substances (opiates).